Consumer Behavior Research of Electronic Money Business in Indonesia and A Marketing Proposal (Subject: Flazz BCA) - Oeshya Lubis, Rizki; Maya Damayanti, Sylviana (The Indonesian Journal of Business Administration, 2016)
Abstract - PT XL Axiata Tbk. is a company that provide telecommunication services in Indonesia. Providing 2G and 3G services that majority Indonesian used. Having around 59,000,000 subscribers, XL become the second largest operator in Indonesia. XL focusing in college and schools subscribers, with XL low cost of services. In Indonesia, there is some phenomena that the most expensive cost is going with the most coverage area. The lowest cost always align with smallest coverage area. XL have different approach, XL have lower cost and wider coverage area. This is why subscribers of XL increasing in last 4 years. In 2014, XL increase their debt to ratio 2.1 to equity. This debt make financial ratio of PT XL Axiata Tbk worse. PT XL Axiata Tbk generate loss in the end of 2014. This situation happened because XL try to wider their coverage area, to gain mare subscribers. To wider the coverage area, XL need new technology and new BTS (Base Transceiver Station). In the end of 2014 XL have the second rank in the most BTS in Indonesia. No other company can do like what XL do. The goal of XL is â€œto be a leader in providing easy-to-use mobile internet experience at a lower price to Indonesians, with the XL brand having strong appeal to the Emerging Middle Class segmentâ€. The debt is not only make a good impact for XL. In other hand there is negative impact. Financial ratio of XL also get worse and make it look bad in investors. XL shares price declining in September 2014 till New Year of 2015. PT XL Axiata Tbk need to improve their financial performance. Alternative to make a better performance, is with adapting 4G technology. It will cost more to XL to build and buying new technology, but it will worth the effort. With forecasting from 2015-2019 Indonesia market will not increase much in telecommunication, because right now from 3 major company in telecommunication, there recording around 250,000,000 SIM card that registered although population in Indonesia only have around 240,000,000 citizens. It means every Indonesians have 1 SIM card minimum. So to get new subscribers the only way is to offering new service that can attract customers to subscribe to XL. 4G will make the new experience to subscribers, and give better internet speed. With this alternative, calculated the cost and revenue of 4G technology with forecasting growth of subscribers and BTS, will give better financial performance and ratios. To apply this strategy, XL need some implementation plan. Some activity need to be done first such as debt extension, looking for new source of funding such as convertible bonds to increase revenue and make net profit. Significant revenue will make operating profit generate profit.Â Keywords: Financial Ratio, WACC, DuPont Analysis, Financial Leverage, Root Cause Analysis, XL, 2G, 3G, 4G, Base Transceiver Station, SIM card, Subscribers